Emergence of a novel PRRSV-1 strain in mainland China: A recombinant strain derived from the two commercial modified live viruses Amervac and DV - Sun, Qi; Xu, Hu; Li, Chao; Gong, Bangjun; Li, Zhen; Tian, Zhi-Jun; Zhang, Hongliang (Frontiers in Veterinary Science, 2022)
Porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) is one of the main pathogens causing porcine reproductive and respiratory syndrome (PRRS). In recent years, the detection number of PRRSV-1 in China has gradually increased, and the PRRSV-1 strains reported in China belong to subtype Ⅰ (Global; Clade A-L). In the present study, a novel PRRSV-1 strain, TZJ2134, was found during epidemiological surveillance of PRRSV-1 in Shandong Province in China. We obtained two fragments of TZJ2134: TZJ2134-L12 (located at nt 1672-nt 2112 in the partial Nsp2 gene) and TZJ2134-(A+B) (located at nt 7463-nt 11272 in the partial Nsp9, complete Nsp10 and partial Nsp11 genes). Phylogenetic and recombination analyses based on the two sequences showed that TZJ2134 is a recombinant strain derived from two commercial PRRSV-1 modified live vaccine (MLV) strains (the Amervac vaccine and DV vaccine strains), forming a new recombinant subgroup of DV+Amervac-like isolates with other strains. However, PRRSV-1 MLV is not currently allowed for use in China. We speculated that TZJ2134 might have been introduced from Europe. This study is the first to provide information on two recombinant PRRSV-1 MLV strains in China and provides new data for the epidemiological study of PRRSV-1 in China.